Grace Aguilar's double-vision to a feminized religiosity through the Torah's laws on inheritance and vows. (June 2019) - Lee, Bernon
Grace Aguilar's interpretation of the Torah's laws on female inheritance and a daughter's vows in her 19th-century biography of biblical women The Women of Israel sits between a proselytizing Anglo-Protestant rhetoric and an androcentric Judaism. This article traces the contours of her feminized, contemplative brand of Judaism through her reading of these laws. The article finds her arguments against the main currents of Judaism of the period to be of a social-religious strain familiar to, yet contending with, the 'tolerant' Christianity of Victoria's England. In staking her space between traditions, Aguilar adopts (and adapts) the terminology of Christian parlance and the Christianized domestic ideology the terms facilitate. The result is a subversive, if ambivalent, work of biblical interpretation that seconds a hegemonic cultural vision for domestic accord in substituting Judaism for its religious heart. Aguilar's recovered 'authentic' Judaism, then, emerges as Christianity's worthy twin that stands its ground against misogyny.